Dynamics of dependence of Russian economy on imports of raw materials - A. Vladimirova; I. Rodina (Вестник университета)
The article examines the dynamics of dependence of Russian economy on imported raw materials, materials, purchased semi-finished products and components used for the production of products (goods, works and services). Examines the impact of the factors determining the dynamics, namely, the territorial structural changes and changes of specific weights of imports of raw materials in the territorial context.